2012
DOI: 10.22358/jafs/66108/2012
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and nutritional characteristics of different types of DDGS for ruminants

Abstract: In this study, different types of cereal grains (maize, wheat, triticale), and their respective distillers dried grains with solubles (DDGS: DDGSM, DDGSW, DDGST) were used. Their effects on parameters expressing nutritional value for ruminants were assessed. The chemical composition of the DDGS was significantly differed (P<0.01), similarly as that of the cereal grains. The DDGS from maize was the highest in fat ( kg -1 DM). The DDGS were three times higher in PDIN values than the original grains (P<0.01). DDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…The comparison of the energy values for distiller's grains with their parental grains is controversial. Some studies have reported that the energy content of distillers' grain reaches or is higher than the energy content of the parental grain, whereas other studies show opposite results . These differences can be a result of the different industrial production processes and the method used to estimate energy.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The comparison of the energy values for distiller's grains with their parental grains is controversial. Some studies have reported that the energy content of distillers' grain reaches or is higher than the energy content of the parental grain, whereas other studies show opposite results . These differences can be a result of the different industrial production processes and the method used to estimate energy.…”
Section: Resultsmentioning
confidence: 98%
“…Prolamins have a variable percentage of monomeric proteins and proteins highly cross‐linked by disulfide bonds . A moderate to high content of proteins linked by disulfide bonds may explain the lowest value of soluble protein of SG in comparison with other cereals grains; therefore, the low SCP in WSDG is expected. Changes in the content of CP sub‐fractions in distillers' grains may be caused by the addition of nitrogen componentsand/or temperature during the ethanol production process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Research Council (NRC, 2001) model assumes a UDP digestibility of 80% for DDGS and the UK Feeding System 90% (AFRC, 1993) for all feeds, whereas the German Protein System assumes a UDP ID of 85% for all feedstuff (Gesellschaft für Ernährungsphysiologie (GfE), 2001). Chrenková et al (2012) determined the ID of five wheat-DDGS, with the mobile bag procedure ranging from 79.6% to 92.2%. The French protein system uses a value of ID of UDP of 85% for wheat-DDGS (Sauvant et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of two new coproducts on the feedstuffs market triggered a series of specific studies. Such studies may refer to the influence of the raw material, e.g., sorghum or wheat instead of corn (2,55), but only studies on corn were considered for the present review.…”
Section: Effects On Ruminant Yieldsmentioning
confidence: 99%